Reframing Gun Violence in South Africa from the Prism of Cultural Violence - Oyinloye, Olaoluwa Babatunde A.; Afolabi, Muyiwa B. (African Journal of Stability and Development (AJSD), 2018)
This article examines gun violence in South Africa from different perspectives of violence looking at the works of several scholars including Galtung, Krug, Anthony Collins and the Australian gun buyback policy. It also examined the inter-relationships between gun violence and the non-criminal societal permissible violence forms. In doing these, the study deconstructed the concept of violence beyond the generally well documented and most recognised physical form of violence and went on to establish similarities and points of divergence between nonviolence and violence. The article deduced that violence is not strange to the human race but it is rather often advocated and that addressing it requires a holistic approach. This is because the type of violence which is abhorred is usually an extension of the societal permissible violence termed cultural violence. The article also made some recommendations about the need for nonviolent conflict engagement through the science of peace which shows there are always more effective alternatives to violence and advocates that peace education be included in South African schools to build the societal fabric of peace.